Lycopus lucidus Turcz Inhibits the Osteoclastogenesis in RAW 264.7 Cells and Bone Loss in Ovariectomized Rat Model - Jeong, Da-Won (Evid Based Complement Alternat Med, 2019)
Lycopus lucidus (LL) is a perennial herb that is traditionally used in Asia to treat edema, wound healing, and gynecological diseases such as irregular menstruation and menstrual pain. We hypothesized that LL would decrease the risk of developing osteoporosis, which is a condition related to gynecological diseases. In this study, we aimed to investigate the effect of a water extract of LL on osteoclastogenesis in vitro and osteoporosis in vivo. In vitro study, we used RAW 264.7 cells as osteoclast precursor cell. Osteoclast differentiation was induced by receptor activator nuclear factor-kappa B ligand (RANKL). We investigated the effect of LL on RANKL-induced osteoclastogenesis, tartrate-resistant acid phosphatase (TRAP) activity, and osteoclast-related genes. In vivo study, we used ovariectomized- (OVX-) induced osteoporosis rat model. OVX-induced Sprague-Dawley rats were randomly separated into sham, OVX, 17β-estradiol (100 μg/kg), wLL-L (15.2 mg/kg), and wLL-H (152 mg/kg) groups. Drugs were administered orally once daily for 9 weeks. wLL inhibited the formation of TRAP-positive osteoclasts; TRAP activity; pit formation; transcription factors (the nuclear factor of activated T-cell cytoplasmic 1 and c-fos); and osteoclast-related genes such as TRAP, carbonic anhydrase II, cathepsin K, osteoclast-associated receptor, and the d2 isoform of the vacuolar ATPase Vo domain. Also, wLL prevented loss of the trabecular area in the OVX femur without change of estrogen level. These results indicate that wLL is able to inhibit osteoclastogenesis and protect bone loss in the OVX-induced osteoporosis model without the influence of hormones like estrogen.